2019
DOI: 10.1016/j.forsciint.2019.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about error rates and human judgment in forensic science

Abstract: Forensic science techniques are often used in criminal trials to infer the identity of the perpetrator of crime and jurors often find this evidence very persuasive. Unfortunately, two of the leading causes of wrongful convictions are forensic science testing errors and false or misleading forensic testimony (Saks & Koehler, 2005). Therefore, it is important to understand jurors' pre-existing beliefs about forensic science, as these beliefs may impact how they evaluate forensic evidence in the courtroom. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 45 publications
4
41
0
2
Order By: Relevance
“…Yet, they are likewise vulnerable to cognitive bias (e.g., [3,56,57]). Moreover, laypeople seem to view bitemark and fingerprint evidence as equally compelling: Koehler (38) found that laypeople believed both fingerprint and bitemark identification errors to be exceptionally rare (1 in 5.5 million and 1 in 1 million, respectively), and Ribeiro et al (58) found that laypeople perceived fingerprint and bitemark identification as equally accurate (88% vs. 89%, respectively) and as entailing a comparable degree of subjective judgment.…”
mentioning
confidence: 99%
“…Yet, they are likewise vulnerable to cognitive bias (e.g., [3,56,57]). Moreover, laypeople seem to view bitemark and fingerprint evidence as equally compelling: Koehler (38) found that laypeople believed both fingerprint and bitemark identification errors to be exceptionally rare (1 in 5.5 million and 1 in 1 million, respectively), and Ribeiro et al (58) found that laypeople perceived fingerprint and bitemark identification as equally accurate (88% vs. 89%, respectively) and as entailing a comparable degree of subjective judgment.…”
mentioning
confidence: 99%
“…249 Recent empirical research reinforces the view that the public is beginning to see the forensic sciences as less believable. 250 The ways in which forensic science's two most closely allied fields (i.e., mainstream science and law) have dealt with issues of trust may be instructive. In science, the open science movement is surely very much about the reliability and democratization of knowledge.…”
Section: Part VI Conclusion: Improving Trust and Efficiency In Expermentioning
confidence: 99%
“…It is best to be able to explain these issues outside of the intense glare and emotion of high profile cases, when tests and investigations not essential to making a determination of the cause and manner of death may be performed if only to settle the publics reservations about the integrity of the entire process Given the imperative to educate the public about the functions of forensic pathologists within the medicolegal and public health surveillance systems, why not seize the opportunity to fundamentally alter how we communicate by engaging with the public? Are the often inaccurate depictions of forensic pathology on television and in the movies, not sufficient motivation for us to educate potential jurors about the capabilities and limitations of contemporary forensic pathology [ 4 , 5 ]? Even though many forensic pathologists are not attached to medical centers nor are they for a variety of reasons involved in research [ 6 ], are we as a community maximizing opportunities to disseminate what research we are involved in to a public and a scientific community that in many ways funds this research and expects evidence based decisions in our reports and in our testimony?…”
Section: Introductionmentioning
confidence: 99%